Comparison of habeas corpus in Malaysia and United Kingdom regarding detainees in relation to security law / Abg Zain Azreen Abg Draup Zamahari ...[et al.] - Abg Draup Zamahari, Abg Zain Azreen; Paizan, Farizah; Ashari, Mazriana; Rusli, Siti Farhana (2009)
Nowadays security laws are questioned on its validity pertaining to the right of Habeas Corpus to the detainees. Historically, both Malaysia and UK practices parliamentary system and derived Habeas Corpus from Magna Carta. Both agrees on Habeas Corpus as one of the fundamental human rights and should not be deprived. Article 5 (2) of the Malaysia federal constitution indicate that Malaysia upheld habeas corpus to secure fundamental right to the people. United Kingdom acknowledges habeas corpus in many laws enacted by the parliament. However, in promoting entrench security to the people living in the both countries, the legislature in both countries have enacted security law that suspend Habeas Corpus. These are known as Internal Security Act in Malaysia and Preventive of Terrorist Act in United Kingdom. To what extend these provisions varied with regard to the right of Habeas Corpus? Are there any differences between the two? This research focuses on the comparison of Habeas Corpus in Malaysia and United Kingdom pertaining to the issue of security law. This research will examine the security law, the procedural part, courts system, and its jurisdiction with reference to statutes and decided cases. The final outcome from this research is that, there are major differences between Malaysia and United Kingdom on the application of Habeas Corpus pertaining to the security law that is on how courts grant decision on Habeas Corpus to detainees.